Three-phase sodium ion battery positive electrode material and preparation method thereof, positive electrode, and sodium ion battery

By preparing NaxSb0.03MnO1.93F0.07 positive electrode material with a three-phase hybrid structure of tunnel phase, P2 phase and O3’ phase, the phase change problem of sodium ion battery positive electrode material during sodium ion deintercalation is solved, and a battery with high capacity and good cycle performance is achieved.

CN119400849BActive Publication Date: 2025-05-02ZHUJI PAWA NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411978940.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-05-02
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have phase transition problems during the sodium ion deintercalation process, resulting in a decrease in rate performance and capacity.

Method used

A three-phase sodium ion battery positive electrode material with chemical formula NaxSb0.03MnO1.93F0.07 was used to prepare a three-phase hybrid structure of tunnel phase, P2 phase and O3’ phase through spray pyrolysis and sintering.

Benefits of technology

It achieves high discharge specific capacity and good cycling performance, making up for the defects of single-phase structural materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400849B_ABST
    Figure CN119400849B_ABST
Patent Text Reader

Abstract

The present invention provides a positive electrode material for a three-phase sodium-ion battery, a preparation method thereof, a positive electrode, and a sodium-ion battery. The chemical formula of the positive electrode material for the three-phase sodium-ion battery is Na x Sb 0.03 MnO 1.93 F 0.07 , where the value of x ranges from 0.68 to 0.88. The positive electrode material for the three-phase sodium-ion battery has a three-phase mixed-phase structure of a tunnel phase, a P2 phase, and an O3' phase. Through the control of elements and dosages, the formation of the three-phase structure is promoted, the defects of single-phase structure materials are compensated, and excellent comprehensive electrochemical performance is obtained. The positive electrode material for the three-phase sodium-ion battery has a high discharge specific capacity and good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery materials, and in particular relates to a positive electrode material for a three-phase sodium ion battery. Background Art

[0002] The layered transition metal oxides for the positive electrode of sodium-ion batteries are mainly of P2, O3 and P3 types, where "P" and "O" refer to the occupied positions of sodium ions, namely prism and octahedron, respectively.

[0003] The P2 and O3 phase structures have their own advantages and disadvantages. There is a certain amount of Na in the P2 phase manganese-based layered oxide. + Vacancies. Sodium ions diffuse in the triangular prisms of the P2 phase by slip. + The diffusion barrier is low and the ionic conductivity is high. However, there is a serious phase transition in the P2 phase manganese-based layered oxide. This phase transition mainly refers to the fact that different Na contents will form an ordered structure with Na vacancies and the sliding of transition metal layers during the sodium ion deintercalation process. This phase transition will cause a decrease in rate performance and capacity. The tunnel type has a large three-dimensional tunnel structure that allows sodium ions to be quickly extracted and embedded, so the tunnel phase has excellent rate performance and cycle stability, but due to the low sodium content, the capacity is also correspondingly low; the O3 phase exhibits high capacity but poor Na + migrate. Summary of the invention

[0004] In response to the above technical problems, the present application provides a three-phase sodium ion battery positive electrode material and a preparation method thereof, a positive electrode, and a sodium ion battery.

[0005] To achieve the above objectives, this application proposes the following technical solutions:

[0006] In a first aspect, a three-phase sodium ion battery positive electrode material is provided, wherein the chemical formula of the three-phase sodium ion battery positive electrode material is Na x Sb 0.03 MnO 1.93 F 0.07 , wherein the value of x is 0.68~0.88, and the three-phase sodium ion battery positive electrode material has a three-phase mixed structure of tunnel phase, P2 phase and O3' phase.

[0007] In a second aspect, a method for preparing a positive electrode material for a three-phase sodium ion battery is provided, comprising:

[0008] Using sodium source, antimony source, manganese source, sodium fluoride and water as raw materials, a mixed solution is prepared;

[0009] The mixed liquid is used as a raw material to carry out spray pyrolysis to obtain a powder;

[0010] The powder is sintered in an oxidizing atmosphere to obtain a three-phase sodium ion battery positive electrode material.

[0011] Furthermore, the temperature of the spray pyrolysis is 600-700°C.

[0012] Furthermore, the carrier gas for the spray pyrolysis is one or more of compressed air, compressed nitrogen, and compressed argon.

[0013] Furthermore, the flow rate of the carrier gas is 2~6L / min.

[0014] Furthermore, the sintering temperature is 750-850°C.

[0015] Furthermore, the sintering time is 18 to 24 hours.

[0016] Furthermore, the oxidizing atmosphere is an air atmosphere or an oxygen atmosphere.

[0017] Furthermore, the manganese source is one or more of manganese nitrate and its hydrate, manganese acetate and its hydrate, manganese carbonate and its hydrate, and manganese oxalate and its hydrate.

[0018] Furthermore, the sodium source is one or more of sodium carbonate, sodium nitrate, sodium acetate, and sodium oxalate.

[0019] Furthermore, the antimony source is antimony trioxide.

[0020] Furthermore, the total metal ion concentration in the mixed solution is 0.5-2 mol / L.

[0021] Furthermore, the molar ratio of sodium in the sodium source to manganese in the manganese source is 0.68-0.88:1.

[0022] Furthermore, the molar ratio of manganese in the manganese source, antimony in the antimony source and sodium fluoride is 0.03:1:0.07.

[0023] In a third aspect, a positive electrode is provided, comprising the aforementioned three-phase sodium ion battery positive electrode material or the three-phase sodium ion battery positive electrode material prepared by the aforementioned preparation method.

[0024] In a fourth aspect, a sodium ion battery is provided, including a positive electrode.

[0025] Compared with the prior art, one or more of the above technical solutions can achieve at least one of the following beneficial effects:

[0026] Provide a sodium ion battery positive electrode material Na with a tunnel phase-P2 phase-O3' phase three-phase mixed structure x Sb 0.03 MnO 1.93 F 0.07By controlling the elements and dosage, the formation of a three-phase structure is promoted, the defects of single-phase structural materials are compensated, and excellent comprehensive electrochemical performance is obtained. Specifically, the positive electrode material has a high discharge specific capacity and good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 XRD diagrams of the positive electrode materials prepared in Example 1 and Comparative Example 2;

[0029] Figure 2 XRD diagram of the positive electrode material prepared in Comparative Example 1;

[0030] Figure 3 XRD local comparison diagram of the positive electrode materials prepared in Example 1 and Comparative Example 1;

[0031] Figure 4 This is the SEM image of the positive electrode material prepared in Example 1.

[0032] Figure 5 The cycle curves of the batteries assembled with the positive electrode materials prepared in the embodiments and comparative examples are shown. DETAILED DESCRIPTION

[0033] After research, the applicant successfully synthesized a sodium ion battery positive electrode material with a three-phase mixed structure of tunnel phase, P2 phase and O3' phase by regulating the element content of Na, Sb, Mn and F. This positive electrode material makes up for the defects of single-phase structure materials, obtains excellent comprehensive electrochemical properties, has a high discharge specific capacity and good cycle performance.

[0034] The present invention provides a three-phase sodium ion battery positive electrode material, wherein the chemical formula of the three-phase sodium ion battery positive electrode material is Na x Sb 0.03 MnO 1.93 F 0.07 , wherein the value of x is 0.68~0.88, and the three-phase sodium ion battery positive electrode material has a three-phase mixed structure of tunnel phase, P2 phase and O3' phase.

[0035] Preferably, the value of x is 0.68-0.75, for example, 0.68, 0.69, 0.70, 0.71, 0.72, 0.73, 0.74, 0.75, etc.

[0036] The present invention also provides a method for preparing a positive electrode material for a three-phase sodium ion battery, comprising:

[0037] Using sodium source, antimony source, manganese source, sodium fluoride and water as raw materials, a mixed solution is prepared;

[0038] The mixed liquid is used as a raw material to carry out spray pyrolysis to obtain a powder;

[0039] The powder is sintered in an oxidizing atmosphere to obtain a three-phase sodium ion battery positive electrode material.

[0040] In some preferred embodiments, the temperature of the spray pyrolysis is 600-700°C. Specifically, the temperature inside the pyrolysis furnace used for spray pyrolysis is 600-700°C, for example, 600°C, 630°C, 650°C, 680°C, 700°C, etc.

[0041] In some preferred embodiments, the carrier gas for spray pyrolysis is one or more of compressed air, compressed nitrogen, and compressed argon.

[0042] In some preferred embodiments, the flow rate of the carrier gas is 2 to 6 L / min, for example, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, etc.

[0043] In some preferred embodiments, the sintering temperature is 750-850°C, for example, 750°C, 780°C, 800°C, 820°C, 850°C, etc.

[0044] In some preferred embodiments, the sintering time is 18 to 24 hours, for example, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, etc.

[0045] In some embodiments, the oxidizing atmosphere is an air atmosphere or an oxygen atmosphere.

[0046] In some embodiments, the manganese source is one or more of manganese nitrate and its hydrate, manganese acetate and its hydrate, manganese carbonate and its hydrate, and manganese oxalate and its hydrate.

[0047] In some embodiments, the sodium source is one or more of sodium carbonate, sodium nitrate, sodium acetate, and sodium oxalate.

[0048] In some embodiments, the antimony source is antimony trioxide.

[0049] In some preferred embodiments, the total metal ion concentration in the mixed solution is 0.5-2 mol / L.

[0050] In some preferred embodiments, the molar ratio of sodium in the sodium source to manganese in the manganese source is 0.68-0.88:1, preferably 0.68-0.75:1, for example, 0.68:1, 0.69:1, 0.70:1, 0.71:1, 0.72:1, 0.73:1, 0.74:1, 0.75:1, etc.

[0051] In some preferred embodiments, the molar ratio of manganese in the manganese source, antimony in the antimony source and sodium fluoride is 0.03:1:0.07.

[0052] In some embodiments, the preparation of the mixed solution is performed with the assistance of at least one mechanical force of stirring and ultrasound. The mixed solution can be a solution or a suspension, etc. The properties of the mixed solution are determined by the properties of the materials. When all the materials are soluble materials, a solution is obtained, and when at least one of the materials is an insoluble substance, a suspension is obtained.

[0053] The present invention also provides a positive electrode, comprising the aforementioned three-phase sodium ion battery positive electrode material or the three-phase sodium ion battery positive electrode material prepared by the aforementioned preparation method.

[0054] The present invention also provides a sodium ion battery, comprising the above-mentioned positive electrode.

[0055] In order to facilitate the understanding of the present invention, the present invention will be described in more comprehensive and detailed manner below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present invention is not limited to the following specific embodiments.

[0056] Example 1

[0057] Step 1: Sodium carbonate, antimony trioxide, manganese carbonate and sodium fluoride were weighed in a molar ratio of 0.68:0.03:1:0.07, placed in water, stirred and ultrasonically treated to prepare a mixed suspension with a total metal ion concentration of 0.5 mol / L.

[0058] Step 2: Turn on the spray pyrolysis furnace, send the mixed liquid into the atomizer for atomization treatment, and then use the carrier gas to send the atomized droplets into the spray pyrolysis furnace for pyrolysis reaction to obtain a spray pyrolysis powder material. The compressed air carrier gas flow rate is 2L / min, and the pyrolysis furnace temperature is 600°C.

[0059] Step 3: Sinter the spray pyrolysis powder material in an air atmosphere at 800°C for 18 hours, and then cool it naturally to obtain the final product.

[0060] The XRD pattern of the obtained product is as follows Figure 1 The SEM image of the obtained product is shown in Figure 4 As shown. Figure 1 It can be seen that the product includes P2 phase, tunnel phase and O3' phase. Figure 4 It can be seen that in addition to flake-like particles (P2 type and O3' type), the material also exhibits a large number of rod-like particles (tunnel type), which further proves the successful synthesis of the tunnel phase-P2 phase-O3' phase three-phase mixed structure material.

[0061] Example 2

[0062] Step 1: Sodium carbonate, antimony trioxide, manganese carbonate and sodium fluoride were weighed in a molar ratio of 0.7:0.03:1:0.07, placed in water, stirred and ultrasonically treated to prepare a mixed suspension with a total metal ion concentration of 1 mol / L.

[0063] Step 2: Turn on the spray pyrolysis furnace, send the mixed liquid into the atomizer for atomization treatment, and then use the carrier gas to send the atomized droplets into the spray pyrolysis furnace for pyrolysis reaction to obtain a spray pyrolysis powder material. The compressed air carrier gas flow rate is 4L / min, and the pyrolysis furnace temperature is 650°C.

[0064] Step 3: Sinter the spray pyrolysis powder material in an air atmosphere at 750°C for 18 hours, and then cool it naturally to obtain the final product.

[0065] Example 3

[0066] Step 1: Sodium acetate, antimony trioxide, manganese acetate and sodium fluoride were weighed in a molar ratio of 0.884:0.03:1:0.07, placed in water, stirred and ultrasonically treated to prepare a mixed suspension with a total metal ion concentration of 2 mol / L.

[0067] Step 2: Turn on the spray pyrolysis furnace, send the mixed liquid into the atomizer for atomization treatment, and then use the carrier gas to send the atomized droplets into the spray pyrolysis furnace for pyrolysis reaction to obtain a spray pyrolysis powder material. The compressed air carrier gas flow rate is 6L / min, and the pyrolysis furnace temperature is 700°C.

[0068] Step 3: Sinter the spray pyrolysis powder material in an air atmosphere at 850°C for 24 hours, and then cool it naturally to obtain the final product.

[0069] Comparative Example 1

[0070] Step 1: Sodium carbonate and manganese carbonate were weighed at a molar ratio of 0.68:1, placed in water, stirred and ultrasonically treated to prepare a mixed solution with a total metal ion concentration of 0.5 mol / L.

[0071] Step 2: Turn on the spray pyrolysis furnace, send the mixed liquid into the atomizer for atomization treatment, and then use the carrier gas to send the atomized droplets into the spray pyrolysis furnace for pyrolysis reaction to obtain a spray pyrolysis powder material. The compressed air carrier gas flow rate is 2L / min, and the pyrolysis furnace temperature is 600°C.

[0072] Step 3: Sinter the spray pyrolysis powder material in air atmosphere at 800℃ for 18h, and then cool naturally to obtain the final product. The XRD pattern of the obtained product is as follows: Figure 2 As shown, from Figure 2 It can be seen that the synthesized sodium battery positive electrode material is a P2 phase material.

[0073] Comparative Example 2

[0074] Step 1: Sodium carbonate, antimony trioxide and manganese carbonate were weighed in a molar ratio of 0.68:0.03:1, placed in water, stirred and ultrasonically treated to prepare a mixed suspension solution with a total metal ion concentration of 0.5 mol / L.

[0075] Step 2: Turn on the spray pyrolysis furnace, send the mixed liquid into the atomizer for atomization treatment, and then use the carrier gas to send the atomized droplets into the spray pyrolysis furnace for pyrolysis reaction to obtain a spray pyrolysis powder material. The compressed air carrier gas flow rate is 2L / min, and the pyrolysis furnace temperature is 600°C.

[0076] Step 3: Sinter the spray pyrolysis powder material in air atmosphere at 800℃ for 18h, and then cool naturally to obtain the final product. The XRD pattern of the obtained product is as follows: Figure 1 As shown, from Figure 1 It can be seen that the sodium ion battery positive electrode material prepared in this comparative example is a two-phase mixed material of tunnel phase and P2 phase.

[0077] contrast Figure 1 and Figure 2 It was found that according to the ratio of sodium source: antimony source: manganese source: fluorine source of 0.68:0.03:1:0.07, a sodium ion battery positive electrode material with a tunnel phase-P2 phase-O3' phase three-phase mixed structure can be prepared. When only manganese source and sodium source are used as raw materials, the sodium ion battery positive electrode material prepared according to the ratio is a P2 phase single-phase material. When manganese source, sodium source and antimony source are used as raw materials, the positive electrode material prepared according to the ratio is a tunnel phase and P2 phase two-phase mixed material. After analysis, the reason for this phenomenon is: due to Sb replacing Na + (1.02 A) site, the more positively charged Sb 3+ It leads to ion rearrangement, inducing a large number of tunnel structures during the synthesis process, and doping with an appropriate amount of Sb and fluorine at the same time. The two elements are doped in a certain proportion and can simultaneously induce the formation of tunnel phase and O3' phase in the absence of sodium, forming a thermodynamically stable configuration of three-phase coexistence.

[0078] Figure 3 The XRD local comparison diagram of Example 1 and Comparative Example 1 shows that after the addition of Sb source, the characteristic peak shifts to the right, indicating that the interlayer space is reduced and Sb 3+The positive charge of the nearby O 2- The layer shows a stronger "pillar effect", indicating that Sb replaces Na + site, therefore, according to the raw material ratio in Example 1, it can be known that the chemical formula of the prepared positive electrode material is Na 0.68 Sb 0.03 MnO 1.93 F 0.07 .

[0079] The positive electrode active materials, Super P and PVDF prepared in each embodiment and comparative example were weighed in a mass ratio of 8: 1: 1, and the weighed PVDF was dissolved in an appropriate amount of NMP. Next, the NMP solution of the positive electrode active materials, Super P and PVDF was fully mixed and ground in an agate mortar for 30 min, and then the fully ground slurry was evenly coated on the aluminum foil, and the coated aluminum foil was kept in a vacuum drying oven at 60 ° C for about 10 h until the organic solvent was completely volatilized, and finally the electrode sheet was cut into a circular electrode sheet with a diameter of 14 mm and rolled once under a roller press. The assembly of the standard CR2025 button cell was completed in a glove box filled with argon. The battery diaphragm uses Celgard 2400 diaphragm, the battery negative electrode uses metal sodium sheet, the electrolyte includes NaPF6 and solvent, the concentration of NaPF6 in the electrolyte is 1 mol / L, the solvent includes PC (propylene carbonate), EMC (ethyl methyl carbonate) and FEC (fluoroethylene carbonate), among which the volume ratio of PC and EMC is 1:1, and FEC accounts for 4% of the total volume of the solvent.

[0080] The assembled battery was subjected to electrical performance testing with a charge and discharge voltage range of 2.0 to 4 V, a current density of 1C, a constant test temperature of 25°C, and 50 cycles.

[0081] The cycle curves of the batteries assembled with the positive electrode active materials prepared in the examples and comparative examples are shown in FIG. Figure 5 As shown, from Figure 5 It can be seen that the batteries assembled with the positive electrode materials prepared in Examples 1 to 3 have high specific capacity and good cycle performance. Compared with the P2 phase sodium-based positive electrode material prepared in Comparative Example 1, the battery assembled with the three-phase sodium-based positive electrode material prepared in Example 1 has a lower first discharge specific capacity, but significantly improved cycle performance. Compared with the P2 phase and tunnel phase two-phase mixed sodium-based positive electrode material prepared in Comparative Example 2, the battery assembled with the three-phase sodium-based positive electrode material prepared in Example 1 not only has an improved first discharge specific capacity, but also significantly improved cycle performance.

[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A three-phase sodium ion battery positive electrode material, characterized in that: The chemical formula of the positive electrode material of the three-phase sodium ion battery is Na x Sb 0.03 MnO 1.93 F 0.07 , wherein the value of x is 0.68-0.88, the three-phase sodium ion battery positive electrode material has a three-phase mixed structure of tunnel phase, P2 phase and O3' phase; the preparation method of the three-phase sodium ion battery positive electrode material comprises: Using sodium source, antimony source, manganese source, sodium fluoride and water as raw materials, a mixed solution is prepared; The mixed liquid is used as a raw material to carry out spray pyrolysis to obtain a powder; The powder is sintered in an oxidizing atmosphere to obtain a three-phase sodium ion battery positive electrode material.

2. The method for preparing a three-phase sodium ion battery positive electrode material according to claim 1, characterized in that: include: Using sodium source, antimony source, manganese source, sodium fluoride and water as raw materials, a mixed solution is prepared; The mixed liquid is used as a raw material to carry out spray pyrolysis to obtain a powder; The powder is sintered in an oxidizing atmosphere to obtain a three-phase sodium ion battery positive electrode material.

3. The method for preparing a three-phase sodium ion battery positive electrode material according to claim 2, characterized in that: The temperature of the spray pyrolysis is 600-700°C.

4. The method for preparing a three-phase sodium ion battery positive electrode material according to claim 2, characterized in that: The carrier gas for the spray pyrolysis is one or more of compressed air, compressed nitrogen, and compressed argon; The flow rate of the carrier gas is 2~6L / min.

5. The method for preparing a three-phase sodium ion battery positive electrode material according to claim 2, characterized in that: The sintering temperature is 750-850° C.; the sintering time is 18-24 hours; and the oxidizing atmosphere is air atmosphere or oxygen atmosphere.

6. The method for preparing a three-phase sodium ion battery positive electrode material according to claim 2, characterized in that: The manganese source is one or more of manganese nitrate and its hydrate, manganese acetate and its hydrate, manganese carbonate and its hydrate, manganese oxalate and its hydrate; the sodium source is one or more of sodium carbonate, sodium nitrate, sodium acetate, sodium oxalate; and the antimony source is antimony trioxide.

7. The method for preparing a three-phase sodium ion battery positive electrode material according to claim 2, characterized in that: The total metal ion concentration in the mixed solution is 0.5~2mol / L.

8. The method for preparing a three-phase sodium ion battery positive electrode material according to claim 2, characterized in that: The molar ratio of sodium in the sodium source to manganese in the manganese source is 0.68-0.88:1; The molar ratio of manganese in the manganese source, antimony in the antimony source and sodium fluoride is 0.03:1:0.

07.

9. A positive electrode, characterized in that It includes the three-phase sodium ion battery positive electrode material as claimed in claim 1 or the three-phase sodium ion battery positive electrode material prepared by the preparation method as claimed in any one of claims 2 to 8.

10. A sodium ion battery, characterized in that Comprising the positive electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Tunnel type oxide material, and preparation method and application thereof

    CN104795550A

  • Composite sodium ion battery positive electrode material and preparation method thereof

    CN118263429A